Anlotinib combined with pembrolizumab as first-line treatment for advanced pulmonary sarcomatoid carcinoma: a case report and literature review - Wen, Yingmei; Dong, Yi; Yi, Lina; Yang, Guifang; Xiao, Mengxia; Li, Qingqing; Zhao, Chen; Ye, Dafu; Yao, Yi (Frontiers in Oncology, 2023)
Pulmonary sarcomatoid carcinoma (PSC) is an uncommon variant of non-small cell lung cancer (NSCLC), known for its unfavorable prognosis. Previous studies have elucidated that PSC generally exhibits a significant expression of programmed death-ligand 1 (PD-L1), an elevated tumor mutation burden, and marked vascular invasion. These factors imply the possible effectiveness of treatments like immunotherapy and anti-angiogenic therapy. The subject of this case was a 65-year-old male diagnosed with advanced PSC, characterized by high PD-L1 expression and devoid of known driver gene mutations. Owing to the restrictions imposed by the COVID-19 pandemic, the patient initially underwent home-based treatment with anlotinib, which led to symptomatic improvement after a single treatment cycle. Subsequent hospitalization allowed for the administration of anlotinib plus Pembrolizumab, resulting in a partial response. Radiotherapy was necessitated due to local disease progression. But after 15 cycles of treatment with Pembrolizumab, hyperprogression was observed. The patient’s overall survival spanned 14 months, with no evident adverse reactions to the medications. Genomic analysis revealed potential associations between treatment efficacy and mutations in the TP53, NF1, and MET genes. This case underscores the effectiveness and safety of a first-line treatment regimen combining pan-target anti-angiogenic therapy (anlotinib) with anti-tumor immunotherapy.